Being at work improves stress, craving, and mood for people with opioid use disorder: Ecological momentary assessment during a randomized trial of experimental employment in a contingency-management-based therapeutic workplace. (May 2022) - Bertz, Jeremiah W.; Panlilio, Leigh V.; Stull, Samuel W.; Smith, Kirsten E.; Reamer, David; Holtyn, August F.; Toegel, Forrest; Kowalczyk, William J.; Phillips, Karran A.; Epstein, David H.; Silverman, Kenneth; Preston, Kenzie L.
Abstract: Employment problems are common among people with substance use disorders (SUDs), and improving vocational functioning is an important aspect of SUD treatment. More detailed understanding of the psychosocial benefits of employment may help refine vocational interventions for people with SUDs. Here, we used ecological momentary assessment to measure possible affective improvements associated with work. Participants ( n = 161) with opioid use disorder were randomized to work (job-skills training) in a contingency-management-based Therapeutic Workplace either immediately or after a waitlist delay. Throughout, participants responded via smartphone to randomly scheduled questionnaires. In linear mixed models comparing responses made at work vs. all other locations, being at work was associated with: less stress, less craving for opioids and cocaine, less negative mood, more positive mood, and more flow-like states. Some of these differences were also observed on workdays vs. non-workdays outside of work hours. These results indicate that benefits associated with work may not be restricted to being actually in the workplace; however, randomization did not reveal clear changes coinciding with the onset of work access. Overall, in contrast to work-associated negative moods measured by experience-sampling in the general population, Therapeutic Workplace participants experienced several types of affective improvements associated with work. Highlights: People with opioid use disorder (OUD) often need help with employment problems. We "employed" people with OUD in a contingency-management-based study workplace. We collected randomly timed ratings of stress, craving, and mood via smartphone. Stress, craving, and mood were better at work and, for some endpoints, on workdays. These results highlight some particular benefits of employment for people with OUD.